Pengembangan ERP Untuk Digitalisasi Proses Produksi dan Penjualan Pupuk - Aries Alfian Prasetyo; Laily Ulfiyah; Achmad Afandi; Andhi Setiawan; Muhammad Jauhar Vikri (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Competition in the industrial world after the impact of Covid-19 has become fierce competition. Many companies choose to increase effectiveness and efficiency by implementing digitalization in production and sales activities. PT. Megarhizo Ega Persada is a company that is developing, a company whose main production is liquid organic fertilizer under the brand